Uticaj Gerarda van Swietena na razvoj austrijske medicine tokom 18. vijeka - Bronza, Boro (Scripta Medica, 2021)
Arrival of Doctor Gerard van Swieten in Vienna, in 1745, as new personal physician of the Holy Roman Empress Maria Theresa, was starting point of a huge wave of transformation in the scope of Austrian medicine. Scientific and methodological experience which doctor from Leiden brought in Habsburg capital was so overwhelming that whole structure of medical science was shattered and reconstructed in a much more efficient way. Impact of Van Swieten was a splendid example of dominance of scientific method in the Netherlands, where modern European science gained more ground than anywhere else during the classical era of baroque, throughout the 17th and first half of the 18th century. On the other hand, internal reforms and transformation of Austria, from the mid-18th century, helped a lot in the process of successful reception of new structural ideas. Through this kind of merging, inside of only several decades, Vienna managed to grow into one of leading centres of medical science in Europe and the world.